Docker experience at INFN-Pisa Grid Data Center. Issue 2 (December 2015) - Mazzoni, E.; Arezzini, S.; Boccali, T.; Ciampa, A.; Coscetti, S.; Bonacorsi, D.
Abstract: Clouds and virtualization offer typical answers to the needs of large-scale computing centers to satisfy diverse sets of user communities in terms of architecture, OS, etc. On the other hand, solutions like Docker seems to emerge as a way to rely on Linux kernel capabilities to package only the applications and the development environment needed by the users, thus solving several resource management issues related to cloud-like solutions. In this paper, we present an exploratory (though well advanced) test done at a major Italian Tier2, at INFN-Pisa, where a considerable fraction of the resources and services has been moved to Docker. The results obtained are definitely encouraging, and Pisa is transitioning all of its Worker Nodes and services to Docker containers. Work is currently being expanded into the preparation of suitable images for a completely virtualized Tier2, with no dependency on local configurations.